Prevalence of dysfunction in sensory integration in kindergarten children - Sem S. Surja; Hendry Irawan; Theresia Ilyan; Jessica Fedriani; Satyadharma M. Winata; Irene Irene (Indonesian Pediatric Society, 2013)
Background Children with dysfunction in sensory integration(DSI) have difficulty effectively and efficiently interacting withtheir environment. It has been estimated that 5 to 10% ofchildrenwithout disabilities have DSI. Late assessment and interventionin children with this problem may significantly impact furtherdevelopment. To date, there is no available data on DSI prevalencein Indonesian children, which is crucial for better understandingof the DSI burden in the community.Objective To estimate the prevalence of DSI in North Jakartachildren using standardized screening tools.Methods Parents of kindergarten children from two privateschools in N orth Jakarta were given questionnaire packetsincluding the Family Information Questionnaire and Winnie Dunn'sShort Sensory Profile (SSP) to assess demographic data and parents'perceptions of their children with regards to DSI.Results Of 264 questionnaire packets distributed, 117 packetswere returned (44.3%). Most children were of Chinese ethnicityand aged 3 to 5 years. Of the 117 children, 49 children ( 41.9%)met the criteria for DSI (definite difference), 33 children (28.2%)were in the probable difference category for DSI, and 35 children(29.9%) were in the category of typical performance. The scores forthe parameters of under-responsive and visual/auditory sensitivitywere the most commonly observed in subjects in the definitedifference category. From all questionnaire packets, a total of18.56% of children in selected kindergartens in North Jakartamet the screening criteria for DSI, while an additional 12.5%were likely to have the disorder.Conclusion Based on parental reports, we find that 18.56% ofchildren from two private kindergartens in North Jakarta hadDSI, while an additional 12.5% are likely to have the disorder.